Technology for synthesizing low carbon alcohol and hydrogen as byproduct from coke oven gas - CAO HUIBO; WANG JUNTING; CUI XIAOXI; MA YINGMIN; WANG GUI; LI XIAO (2015)
A technology for synthesizing low carbon alcohol and hydrogen as byproduct from coke oven gas comprises the following steps: compressing the coke oven gas, carrying out desulphurization and decarburization treatment to obtain purified coke oven gas with the H2S content being smaller than 1ppm, allowing the purified coke oven gas to enter a pressure swing adsorption unit in order to remove CH4, allowing removed CH4 and CO2 obtained after purification to enter a coke oven gas reforming unit, reforming, mixing the obtained reformed gas with the coke oven gas obtained after pressure swing adsorption to obtain synthetic gas meeting low carbon alcohol synthesis requirements, carrying out low carbon alcohol synthesis, allowing the obtained low carbon alcohol mixture to enter a low carbon alcohol separation unit, and separating to obtain methanol, ethanol, propanol and butanol products. The technology comprises the advantages of reasonable utilization of the coke oven gas, promotion of energy saving and emission reduction, energy structure adjustment, and obvious improvement of the economic and environmental benefits.